Voluntary disclosure programmes and tax amnesties: an international appraisal - Jaramba, Toddy (Rhodes University, Faculty of Commerce, Department of Accounting, 2014)
Tax amnesties are government programs that typically allow a short period of time for tax evaders to voluntarily repay previously evaded taxes without being subject to penalties and prosecution that discovery of such tax evasion normally brings. Tax amnesties differ widely in terms of coverage, tax types, and incentives offered. A state's Voluntary Disclosure Programme is another avenue available to taxpayers to assist them in resolving their state tax delinquencies. This programme is an on-going programme as compared to a tax amnesty, which is there for a limited time period only. The main goal of the research was to describe the tax amnesty and the voluntary disclosure programmes in South Africa and to assess their advantages and disadvantages. This thesis also discussed another form of voluntary disclosure programme, referred to as an Offshore Voluntary Disclosure Programme, which allows taxpayers with unreported foreign bank accounts, and presumably unreported foreign income, to voluntarily disclose their affairs. The study found that, due to tax amnesties, Government raises more tax revenue not only in the short run from collecting overdue taxes but also by bringing former non-filers back into the tax system for the long run. It was also found that, initially short-run revenue brought in from overdue taxes will be positive for the first amnesty and then decline each time the amnesty is offered repeatedly. The reason for the decline in revenue might be that tax amnesties provide incentives for otherwise honest taxpayers to start evading taxes because they will anticipate the offering of future amnesties, thereby weakening tax compliance. The costs associated with amnesty programmes include negative long run revenue impact and also that amnesty programmes reduce compliance by taxpayers in the long-run. In South Africa tax amnesties, especially the voluntary disclosure programme, are likely to be successful since they will increase the revenue yield and also bring non-filers back on the tax rolls.
Keywords: Tax amnesty -- South Africa; Tax evasion -- South Africa; Investments, Foreign -- Taxation -- South Africa; Tax collection -- South Africa; Tax administration and procedure -- South Africa